1991
DOI: 10.1111/j.1749-6632.1991.tb33878.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adenosine and Adenosine Transport in Ethanol‐Induced Cellular Tolerance and Dependence

Abstract: Acute exposure to ethanol in culture inhibits adenosine uptake into cells, thereby increasing the concentration of extracellular adenosine. Extracellular adenosine then reacts with adenosine A2 receptors to stimulate intracellular cAMP production. During prolonged exposure to ethanol, the increase in cAMP is followed by the development of heterologous desensitization of receptors coupled to adenylyl cyclase via Gs, the stimulatory GTP-binding protein. Ethanol-induced heterologous desensitization appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…In contrast, chronic ethanol exposure to cultured cells no longer increases extracellular adenosine levels. Furthermore, chronic exposure decreases type 1 equilibrative nucleoside transporter (ENT1) expression (Diamond et al, 1991). Specifically, mice lacking ENT1 present with reduced adenosine levels in the nucleus accumbens (NAc).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, chronic ethanol exposure to cultured cells no longer increases extracellular adenosine levels. Furthermore, chronic exposure decreases type 1 equilibrative nucleoside transporter (ENT1) expression (Diamond et al, 1991). Specifically, mice lacking ENT1 present with reduced adenosine levels in the nucleus accumbens (NAc).…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde dehydrogenase quickly catalyzes the conversion of acetaldehyde to acetate, and alcohol-dependent individuals show elevated acetate up to 24 hours after the last drink (17). Acetate enters the tricarboxylic acid (TCA) cycle for oxidation via acetyl-CoA synthetase, and the process of oxidation generates adenosine (18)(19)(20)(21), which has sedating properties similar to those of ethanol (22)(23)(24). One may expect heavy drinkers to have long periods of time with elevated levels of adenosine in their tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated the contribution of adenosine receptors to antinociception (DeLander and Wahl, 1988;Gungor et al, 1994;Holmgren et al, 1986;Sawynok and Sweeney, 1989), and at least one study has suggested that adenosinergic antinociception may be modulated by GABA, compounds (Sabetkasai and Zarrindast, 1993). Furthermore, adenosine receptors have been found to be important in the development of tolerance to ethanol (Coe et al, 1996;Diamond et al, 1991;Sapru et al, 1994). Calcium channel blockers have also been reported to produce antinociception (Hunt et al, 1996;Martin et al, 1996;Sawynok et al, 1990).…”
Section: Discussionmentioning
confidence: 97%